Isolation and identification Staphylococcus aureus from Cows ruminal content - Hanaa Khlil (مجلة علوم ذي قار, 2019)
This study was carried out for isolation of Staphylococcus aureus and identification it from Cow΄s ruminal contant through take of specimens and caltured it on (MSA), the percentage of isolation on this media about 52%, Biochemical tests were done. In biotyping test the percentage reveled in type C about 61.5% while in type A 38.4% .The specimens gave 76% for pigment on Milk agar .While in antibiotic tests appeard sensitive 80.76%.